1982
DOI: 10.1016/0304-3959(82)90169-5
|View full text |Cite
|
Sign up to set email alerts
|

Controllability, coping behavior, and stress-induced analgesia in the rat

Abstract: Exposure to painful or stressful stimuli produces an analgesic reaction which can persist for 1-2 h post-stress. In the typical stress-induced analgesia study the subject is not permitted to alter or exert control over the aversive event to which it is exposed. That is, its behavior affects neither the duration or intensity of the event. The experiments reported here attempted to determine whether this inability of the subject to control the aversive event is an important determinant of stress-induced analgesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
2
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(58 citation statements)
references
References 27 publications
1
52
2
3
Order By: Relevance
“…Differences are also found in the brain. Animals which could not cope with a shock exhib ited marked decreases in hypothalamic norepinephrine levels whereas coping animals -in spite of experiencing the same shocks -showed the same levels as seen in rest ing, unstressed control animals [2,21,28,29], Similarly, dopamine levels were markedly affected in the mesocortical and mesolimbic, although not the nigrostriatal, areas of rats unable to cope with the foot shock but were unaf fected in these areas in coping rats which received but could terminate the same shock [9,21,23], Serotonin levels in the septum showed a marked decrease in rats which were not able to cope with a shock but were increased in rats which could cope with the same stressor [17], The opiatc/endorphin system in the brain was markedly activated by uncontrollable electrical shock ex posure whereas only a slight stimulation of this system was observed in rats which could cope with this stressor [13]. In spite of foot shock, brains of coping animals show no, smaller or different stress responses; in particular, the reduction of hypothalamic norepinephrine, which is so typical of animals being exposed to any noncontrollabie stressor, is not present in coping animals.…”
Section: Biochemical Changes Associated With the Ability Or Inabilitymentioning
confidence: 99%
“…Differences are also found in the brain. Animals which could not cope with a shock exhib ited marked decreases in hypothalamic norepinephrine levels whereas coping animals -in spite of experiencing the same shocks -showed the same levels as seen in rest ing, unstressed control animals [2,21,28,29], Similarly, dopamine levels were markedly affected in the mesocortical and mesolimbic, although not the nigrostriatal, areas of rats unable to cope with the foot shock but were unaf fected in these areas in coping rats which received but could terminate the same shock [9,21,23], Serotonin levels in the septum showed a marked decrease in rats which were not able to cope with a shock but were increased in rats which could cope with the same stressor [17], The opiatc/endorphin system in the brain was markedly activated by uncontrollable electrical shock ex posure whereas only a slight stimulation of this system was observed in rats which could cope with this stressor [13]. In spite of foot shock, brains of coping animals show no, smaller or different stress responses; in particular, the reduction of hypothalamic norepinephrine, which is so typical of animals being exposed to any noncontrollabie stressor, is not present in coping animals.…”
Section: Biochemical Changes Associated With the Ability Or Inabilitymentioning
confidence: 99%
“…Several authors have suggested that conditioned analgesia may be related to automatic freezing reactions in animals exposed to stress-provoking stimuli (Foa et al, 1992;Maier et al, 1982). Others have hypothesized a link in both animals and humans between arousal and numbing responses to stressful situations and a variety of physiological changes, including changes in endogenous opioid peptide levels (Ironside, 1980;Pitman, van der Kolk, Orr, & Greenberg, 1990;van der Kolk, Greenberg, Orr, & Pitman, 1989), glucocorticoid levels (Yehuda et al, 1995), hippocampal function (Sapolsky, Hideo, Rebert, & Finch, 1990), and serotonin levels (Gerson & Baldessarini, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Prior exposure to a series of inescapable, but not escapable, shocks has been found to produce a nonopioid analgesic reaction in rats if they are given tail-flick tests immediately after the shock session (Maier, Drugan, & Grau, 1982), and an opioid reaction if tested 24 h later with a brief series of priming shocks . Furthermore, the classicalconditioning of a longterm opioid reaction in rats has been shown to occur in response to environmental or contextual cues, using the helplessness preshock procedure and tail-flick tests of analgesia (Maclennan, Jackson, & Maier, 1980).…”
Section: Discussionmentioning
confidence: 99%